Post-operative morbidity following pancreatic duct occlusion without anastomosis after pancreaticoduodenectomy: a systematic review and meta-analysis. Issue 8 (August 2020) - Giglio, Mariano C.; Cassese, Gianluca; Tomassini, Federico; Rashidian, Nikdokht; Montalti, Roberto; Troisi, Roberto I.
Abstract: Background: Pancreatic duct occlusion (PDO) without anastomosis is a technique proposed to mitigate the clinical consequences of postoperative pancreatic fistulas (POPF) after pancreaticoduodenectomy. The aim of this study was to appraise the morbidity following PDO through a systematic review and meta-analysis. Methods: A systematic search of MEDLINE, Embase, and Web Of Science identified studies reporting outcomes of PDO following pancreaticoduodenectomy. Pooled prevalence rates of postoperative complications and mortality were computed using random-effect modeling. Meta-regression analyses were performed to examine the impact of moderators on the overall estimates. Results: Sixteen studies involving 1000 patients were included. Pooled postoperative mortality was 2.7%. A POPF was reported in 29.7% of the patients. Clinically relevant POPFs occurred in 13.5% of the patients, while intra-abdominal abscess and haemorrhages occurred in 6.7% and 5.5% of the patients, respectively. Re-operation was necessary in 7.6% of the patients. Postoperatively new onset diabetes occurred in 15.8% of patients, more frequently after the use of chemical substances for PDO (p = 0.003). Conclusions: PDO is associated with significant morbidity including new onset of post-operative diabetes. The risk of new onset post-operative diabetes is associated with the use of chemical substance for PDO. Further evidence is needed to evaluate the potential benefits of PDO in patients at high risk of POPF.